Irradiation of 9 Bromo-Fluorene in the Presence of Sensitizers/Quenchers—An Approach to determining Triplet Energy of 9-Bromo-Fluorene - Garg, S.; Kohli, J.C. (Asian Journal of Chemistry, 2010)
Irradiation of 9-bromo-fluorene was done in the presence of a number of sensitizers/quenchers. The triplet energy of 9-bromo-fluorene was found to be equal to or greater than that of fluorenone (53.3 kcal/mole).